CD40 ligand and interferon‐γ induce an antimicrobial response against Mycobacterium tuberculosis in human monocytes. Issue 1 (8th April 2013) - Klug‐Micu, Georgiana M.; Stenger, Steffen; Sommer, Andrea; Liu, Philip T.; Krutzik, Stephan R.; Modlin, Robert L.; Fabri, Mario
Summary The ability of T cells to activate antimicrobial pathways in infected macrophages is essential to host defence against many intracellular pathogens. Here, we compared the ability of two T‐cell‐mediated mechanisms to trigger antimicrobial responses against Mycobacterium tuberculosis in humans, CD40 activation and the release of interferon‐γ (IFN‐γ). Given that IFN‐γ activates a vitamin D‐dependent antimicrobial response, we focused on induction of the key components of this pathway. We show that activation of human monocytes via CD40 ligand (CD40L) and IFN‐γ, alone, and in combination, induces the CYP27b1‐hydroxylase, responsible for the conversion of 25‐hydroxyvitamin D (25D) to the bioactive 1, 25‐dihydroxyvitamin D (1, 25D), and the vitamin D receptor (VDR). The activation of the vitamin D pathway by CD40L and IFN‐γ results in up‐regulated expression of the antimicrobial peptides, cathelicidin and DEFB4, as well as induction of autophagy. Finally, activation of monocytes via CD40L and IFN‐γ results in an antimicrobial activity against intracellular M. tuberculosis. Our data suggest that at least two parallel T‐cell‐mediated mechanisms, CD40L and IFN‐γ, activate the vitamin D‐dependent antimicrobial pathway and trigger antimicrobial activity against intracellular M. tuberculosis, thereby contributing to human host defence against intracellular infection.